Lack of association between HFE gene mutations and hepatocellular carcinoma in patients with cirrhosis. Issue 8 (15th July 2003) - Boige, V; Castéra, L; de Roux, N; Ganne-Carrié, N; Ducot, B; Pelletier, G; Beaugrand, M; Buffet, C
Abstract : Background: Liver cirrhosis may lead to hepatocellular carcinoma (HCC), regardless of its cause. Genetic and/or environmental factors may modulate the risk of HCC. Mutations in the HFE gene are responsible for genetic haemochromatosis, a condition known to be associated with liver cirrhosis, HCC, or both. It has recently been suggested that the C282Y HFE gene mutation may be more frequent in patients with HCC that have developed in the non-cirrhotic liver than in the general population. Whether or not HFE gene mutations are associated with an increased risk of HCC in patients with cirrhosis is unknown. Aim: To assess the prevalence of HFE gene mutations in cirrhotic patients with and without HCC. Patients and methods: A total of 133 consecutive cirrhotic patients with HCC were prospectively studied for the presence of C282Y and H63D mutations. The control group consisted of 100 cirrhotic patients without HCC. We used restriction enzyme digestion of polymerase chain reaction amplified genomic DNA for determination of HFE genotypes. Iron loading was assessed on non- tumoral liver biopsy samples from 89 patients with HCC and 73 patients without HCC. Results: The prevalence of C282Y heterozygotes was similar in patients with and without HCC (5% v 4%, respectively; p=0.65) and did not differ from that expected in the general population. None of the HCC patients was found to be homozygous for C282Y or H63D, nor compound heterozygous. The prevalence of H63D heterozygotes was similar in patients with and without HCC (31% v 38%, respectively; p=0.25). No relation was detected between HFE genotypes and hepatic iron loading in patients with or without HCC. Conclusion: C282Y and H63D mutations do not appear to be associated with an increased risk of HCC in patients with cirrhosis.